2018
DOI: 10.1111/1365-2664.13166
|View full text |Cite
|
Sign up to set email alerts
|

Grazer effects on soil carbon storage vary by herbivore assemblage in a semi‐arid grassland

Abstract: Accounting for 10%–30% of global soil organic carbon, grassland soils potentially present a large reservoir for storing atmospheric CO2. Livestock grazing management can substantially affect grassland soil carbon (C) storage, but few controlled experiments have explored how herbivore assemblages (different herbivore species and combinations) affect soil C storage. We examined effects of moderate grazing by different herbivore assemblages (no grazing; sheep grazing; cattle grazing; mixed grazing by sheep and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 52 publications
0
33
0
1
Order By: Relevance
“…The study was carried out at the Songnen Grassland Ecological Research Station of Northeast Normal University, Jilin Province, PR China (44°35′ N, 123°30′ E). The study site has a semiarid, continental climate with a frost‐free period of about 140 days, annual mean temperature ranging from 4.6 to 6.4°C, and annual precipitation from 280 to 400 mm (Chang et al, ; Huang et al, ; Li et al, ; J. Liu et al, ; Zhong et al, ). The main soil types in the study area include a light Chernozem soil, saline meadow soil, alkaline meadow soil, alkaline saline soil and a Chernozem type sandy soil (pH 8.5–10.0).…”
Section: Methodsmentioning
confidence: 99%
“…The study was carried out at the Songnen Grassland Ecological Research Station of Northeast Normal University, Jilin Province, PR China (44°35′ N, 123°30′ E). The study site has a semiarid, continental climate with a frost‐free period of about 140 days, annual mean temperature ranging from 4.6 to 6.4°C, and annual precipitation from 280 to 400 mm (Chang et al, ; Huang et al, ; Li et al, ; J. Liu et al, ; Zhong et al, ). The main soil types in the study area include a light Chernozem soil, saline meadow soil, alkaline meadow soil, alkaline saline soil and a Chernozem type sandy soil (pH 8.5–10.0).…”
Section: Methodsmentioning
confidence: 99%
“…4B, Table 3). This result emphasises that mixed livestock assemblages deserve particular attention as they can affect plant composition distinctly from single grazing species regimes or alter traveling and trampling behaviours of grazing animals (Chang et al, 2018;Liu et al, 2015).…”
Section: Geophysical Predictors Driving Socmentioning
confidence: 97%
“…4B). Chang et al (2018) found that in a N poor semiarid grassland, sheep decreased SOC content in comparison to cattle due to vegetation changes caused by their feeding preference for highly palatable forbs, promoting less palatable grasses which supported less root biomass. A shift towards higher grass biomass with sheep grazing was also found in the Pyrenees (Sebastia et al, 2008).…”
Section: Geophysical Predictors Driving Socmentioning
confidence: 98%
See 2 more Smart Citations